PEMBUATAN DAN KARAKTERISASI SIFAT FISIS ELEKTRODA KARBON DARI BUNGA RUMPUT GAJAH DITINJAU DARI PERBEDAAN UKURAN PARTIKEL - Taer, E.; Nurjanah, S.; Sugianto, Sugianto; Taslim, R. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Preparation and characterization of physical properties of carbon electrode from flower of elephant grass has been analyzed with variations in particle size. Production of carbon electrodes was begun with pre-carbonization, grinding with hard grinder, grinding with ball milling and followed by sieving process. Variations in particle size selected of <38 µm milling continued during 20 hours, <38 µm (SB), and 39-52 µm (SC). All of the sample have been activated by chemical activating agent with NaOH at a concentration of 0,4 M. Carbonization process was performed at temperatures of 600˚C in the gas environment N2 and followed by physical activation process by using a CO2 gas at a temperature of 850˚C. Physical parameters such as mass, diameter and thickness of activated carbon electrodes was collected at a condition (i) before carbonization, (ii) after carbonization and (iii) after physical activation to found the density characteristic. The results of density data showed that the sample SA of <38 µm has a density value of 1,103 g/ cm3 , (ii) 0,869 g/cm3, (iii) 0,800 g/cm3, SB (i) 1,083 g/ cm3, (ii) 0,816 g/cm3, (iii) 0,728 g/cm3 and SC (i) 1,072 g/ cm3, (ii) 0,777 g/ cm3 and (iii) 0,599 g/ cm3, respectively. As a conclution, the particle size was varies inversely with the density. As an addition, the crystallographic analysis showed that the particle size is inversely proportional to the Lc value. Keywords: particle size, physical characteristic, activated carbon, flower of elephant grass.